Effects of privatization on price and labor efficiency: The Swedish electricity distribution sector - Erik Lundin (Research Institute of Industrial Economics (IFN), 2016)
I examine the effects of privatization, in the form of acquisitions, in the Swedish electricity distribution sector. As the majority of the distribution networks remained publicly owned, I use a synthetic control method to identify the effects on price and labor efficiency. In comparison to their synthetic counterparts, I find that the acquired networks increased labor efficiency by on average 18 percent, while no effect is found on the price. Thus, the evidence suggests substantial efficiency gains but that these are not fed through to consumer prices. Since each acquisition involved several bordering networks that were separately operated by each municipality prior to the acquisitions, I examine to what extent the efficiency gains are likely to be driven by increased economies of scale. Results suggest that the entire effect can be explained by increased economies of scale, questioning the causal effect of privatization per se.
Keywords: L33; L52; L94; 330; Incentive regulation; Electricity distribution; Natural monopoly; Norm model regulation; Privatization; Acquisitions